Pengaruh Marketing Mix Yang Di Mediasi Oleh Kualitas Pelayanan Terhadap Keputusan Pembelian Pada Surya Naufal Farm - Yusuf Saputra; Khairunnisa Khairunnisa (MABIS: Jurnal Manajemen Bisnis Syariah, 2022)
The problem this research is how much influence the marketing mix mediated by service quality has on purchasing decisions at Surya Naufal Farm. The purpose of writing this thesis is to determine the effect of the marketing mix mediated by service quality on purchasing decisions at Surya Naufal Farm. The type of research conducted is field research using a quantitative approach. Data collection techniques using a questionnaire. The population in this study are all Surya Naufal Farm consumers who are domiciled in Koto VII District. The sample in this study was determined by the Cochran formula as many as 97 respondents. The data analysis technique used path analysis. Based on the results of research that has been carried out, it shows that there is a significant influence between the marketing mix variable (X) on the service quality variable (Z) at Surya Naufal Farm, there is a significant influence between the marketing mix variable (X) on the purchasing decision variable (Y) at Surya Naufal Farm, there is a significant influence between the service quality variable (Z) on the purchasing decision variable (Y) at Surya Naufal Farm and there is a significant influence between the marketing mix variable (X) mediated by service quality (Y) on purchasing decisions ( Y) at Surya Naufal Farm.